EFEKTIVITAS APLIKASI BACA SERU DAN ASYIK (BARUSIK) DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF ABJAD PADA ANAK DISABILITAS INTELEKTUAL RINGAN - Ningsih, Fedia Rahma; Taufan, Johandri; Zulmiyetri; Sri Handayani, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Especially for children with modest intellectual disabilities, the ability to recognize letters is a crucial first step in the development of early reading. Because of these constraints, learning materials must be tangible, visually appealing, and captivating. This study's primary goal was to show how the Fun and Fun Reading (BARUSIK) app can help kids with minor intellectual disabilities recognize alphabetic letters. Using an A-B-A design and the Single Subject Research (SSR) experimental method, a quantitative research methodology was employed. An 8-year-old girl in class II at Sungai Banyak State Special Needs School who had modest intellectual difficulties served as the study's subject. Observation was used to gather data, and a performance test was used as a research tool to gauge the child's proficiency in naming and displaying alphabet letters. Data analysis was then displayed graphically. The findings demonstrated that the child's ability stayed constant at 25% at the start of the baseline investigation (A1). In phase B of the intervention, the child's proficiency rises to 70%. The child's abilities continued to grow and stabilized at 90% at the end of the baseline testing (A2). Children with minor intellectual disabilities have been shown to benefit from the Fun and Exciting Reading Application (BARUSIK) in terms of their ability to recognize alphabetic letters. According to this study, children with modest intellectual disabilities should learn in special schools using application-based media.